Hrasti - Quercus spp. - Jurc, Maja (Gozdarski vestnik, 2006)
In the present contribution seven species of butterflies on oaks (Quercus spp.) are presented: gypsy moath (Lymantria dispar), European oak leaf roller (Tortrix viridana), winter moth (Operophthera brumata), mottled umber moth (Erannis defoliaria), oak processionary moth (Thaumetopoea processionea), browntail moth (Euproctis chrysorrhoea) and lackey moth (Malacosoma neustria).L. dispar and T. viridana have appeared several times in the sub-mediterranean and sub-pannonic areas of Slovenia and have caused damage. The next two species cause less significant defoliation mostly in natural pedunculate oak (Quercus robur) stands in Prekmurje and in the Krakovo forest as well as in thermophyllic oak stands in the coastal region. T. processionea, E. chrysorrhoea and M. neustria cause damage on oaks sporadically. Researchers state that butterflies which defoliate forests are appearing more frequently in Europe and are starting to cause extensive damagein forests again. Recently, in Slovenia the situation in oaks forests isthe same. A short description of the insects' morphology, bionomy, a description of damage, possible misidentifications, hosts, their most important natural enemies, causes of beginning or continuation of their outbreaks and their threat to forests are given.
Keywords: hrasti; Quercus sp.; žuželke; metulji